Relationships between Personality Traits, Medial Temporal Lobe Atrophy, and White Matter Lesion in Subjects Suffering from Mild Cognitive Impairment - Duron, Emmanuelle; Vidal, Jean-Sébastien; Bounatiro, Samira; Ben Ahmed, Sana; Seux, Marie-Laure; Rigaud, Anne-Sophie; Hanon, Olivier; Viollet, Cécile; Epelbaum, Jacques; Martel, Guillaume (Frontiers in Aging Neuroscience, 2014)
Mild Cognitive Impairment (MCI) is a heterogeneous cognitive status that can be a prodromal stage of Alzheimer‘s disease (AD). It is particularly relevant to focus on prodromal stages of AD such as MCI, because pathophysiological abnormalities of AD start years before the dementia stage. Medial temporal lobe atrophy (MTL) resulting from AD lesions and cerebrovascular lesions (i.e. white matter lesions (WML), lacunar strokes and strokes) are often revealed concurrently on Magnetic Resonance Imaging (MRI) in MCI subjects. Personality changes have been reported to be associated with MCI status and early AD. More specifically, an increase in neuroticism and a decrease in conscientiousness have been reported, suggesting that higher and lower scores, respectively in neuroticism and conscientiousness are associated with an increased risk of developing the disease. However, personality changes have not been studied concomitantly with pathological structural brain alterations detected on MRI in patients suffering from MCI. Therefore, the objective of the present study was to assess the relationship between MTL atrophy, WML, lacunar strokes and personality traits in such patients. The severity of WML was strongly associated with lower levels of conscientiousness and higher levels of neuroticism. Conversely, no association was detected between personality traits and the presence of lacunar strokes or MTL atrophy. Altogether, these results strongly suggest that personality changes occurring in a MCI population, at high risk of AD, are associated with WML, which can induce executive dysfunctions, rather than with MTL atrophy.